2018
DOI: 10.1038/s41467-018-04108-9
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic cycle in haematopoietic niches promotes initiation of malaria transmission and evasion of chemotherapy

Abstract: Blood stage human malaria parasites may exploit erythropoietic tissue niches and colonise erythroid progenitors; however, the precise influence of the erythropoietic environment on fundamental parasite biology remains unknown. Here we use quantitative approaches to enumerate Plasmodium infected erythropoietic precursor cells using an in vivo rodent model of Plasmodium berghei. We show that parasitised early reticulocytes (ER) in the major sites of haematopoiesis establish a cryptic asexual cycle. Moreover, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 46 publications
9
53
0
Order By: Relevance
“…These data confirm that 280 the V2721F mutation confers ART resistance while the V2752F mutation mediates resistance 281 primarily to CQ and to some extent to ARTs. The recrudescence of the wildtype 820 and G1808 V2721F 282 at 45mg/kg ART is also in agreement with our previous findings, that P. berghei is less sensitive to 283 ARTs, especially in the spleen and bone marrow which could be the source of recrudescent infection 284 at relatively lower doses (Lee et al, 2018). 285 286…”
supporting
confidence: 90%
“…These data confirm that 280 the V2721F mutation confers ART resistance while the V2752F mutation mediates resistance 281 primarily to CQ and to some extent to ARTs. The recrudescence of the wildtype 820 and G1808 V2721F 282 at 45mg/kg ART is also in agreement with our previous findings, that P. berghei is less sensitive to 283 ARTs, especially in the spleen and bone marrow which could be the source of recrudescent infection 284 at relatively lower doses (Lee et al, 2018). 285 286…”
supporting
confidence: 90%
“…In support of the first possibility, it has long been known that gametocytogenesis is increased when parasites are grown in the presence of reticulocytes 42,43 , and this is notable because of the presence of reticulocytes in the bone marrow where gametocytes accumulate 6,7 . In line with this, work in P. berghei has shown there is preferential formation of gametocytes in early reticulocytes within bone marrow 44 . The committed merozoite may have a preference for invasion of reticulocytes that is directed by PfAP2-G which could account for this propensity to develop in the bone marrow.…”
Section: Discussionmentioning
confidence: 53%
“…While Plasmodium gametocyte maturation dynamics had previously not been addressed in detail using animal models, three important advances were achieved over the last 3 years: (i) the use of humanised mouse models to study P. falciparum gametocyte dynamics (Duffier et al, ); (ii) the demonstration that organs involved in erythropoiesis, including the bone marrow are an important reservoir for rodent malaria gametocytes (De Niz et al, ; Lee et al, ); and (iii) the use of IVM to study the dynamics of gametocyte maturation including extravasation, maturation and egress (De Niz et al, ). The IVM study showed that bone locations enriched with red marrow were preferentially colonised by P. berghei , and that bone marrow sinusoids are key sites for sequestration and invasion.…”
Section: Primary Lymphoid Organs In Parasitic Infectionsmentioning
confidence: 99%
“…The spleen has recently gained great interest in the context of malaria transmission. Studies in humanised mice infected with P. falciparum (Duffier et al, ), and rodent models of malaria infected with P. berghei (Lee et al, ), have consistently shown increased numbers of immature gametocytes in the spleen. The relevance of this organ for host‐to‐vector transmission, as well as its study in the context of transmission‐blocking drugs, remains to be fully explored, and IVM could be an extremely relevant tool for this purpose.…”
Section: Secondary Lymphoid Organs In Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation